Special Care Dentistry: attitudes of Specialists in Paediatric Dentistry practising in the UK to the creation of a new specialty - M. L. HUNTER, B. HUNTER, S. A. THOMPSON, & W. S. MCLAUGHLIN (Paediatric Dentistry, 2004)
This study was designed to examine the attitudes of Specialists in Paediatric Dentistry (SPDs) practising in the UK towards the creation of a specialty of Special Care Dentistry (SCD).